Perilaku Adiktif Terhadap Kopi: Studi Kualitatif - Zabrina Zabrina; Roza Eva Susanti (Indo Publishing, 2026)
Coffee consumption has become an integral part of students' lifestyles and is commonly used to improve concentration and academic productivity. However, excessive coffee intake may lead to addictive behavior that negatively affects physical, psychological, and social well-being. This study aims to describe coffee addictive behavior among university students and to develop an intervention plan to reduce caffeine dependence. The study employed a qualitative approach using an intrinsic case study design. Data were collected through in-depth interviews, observations, and documentation involving a 23-year-old participant who routinely consumed more than three cups of coffee per day. Data were analyzed using thematic analysis through data reduction, data presentation, conclusion drawing, and triangulation. The findings revealed several indicators of caffeine addiction, including increased tolerance, withdrawal symptoms, loss of control over consumption, craving, continued coffee consumption despite negative consequences, and impaired social functioning and sleep quality. Academic stress, work demands, and coffee-drinking culture were identified as the primary factors contributing to addictive behavior. As a practical intervention, this study proposes a six-week tapering strategy involving gradual reduction of coffee consumption to minimize withdrawal symptoms and facilitate recovery from caffeine dependence